Age structure of sitophilus oryzae using gultinous rice, calrose rice, Thai red rice and ponni rice / Nur Syakirah Mohamed Elias - Mohamed Elias, Nur Syakirah (2020)
Stored product insect cause more than one fifth of total damages in rice in developing countries commonly and one of the insect that contributes to this problem is rice weevil Sitophilus oryzae. The huge amount of loss could be associated with their biology because their all four larval stage and pupal stage occurred inside the grain. Hence, causing their control and elimination are very difficult. Thus, this study focuses on the rice weevil S. oryzae age structure relationship with morphological characteristic based on the amount of nutrient used which might gain information on the preference and development of rice weevil S. oryzae. Through that, a new process can be developed later to protect the food grain in a better way. The tests were conducting by rearing this species in the four types of rice and were measured according to their age. Rice weevil S. oryzae were exposed to glutinous rice, calrose rice, thai red rice and ponni rice. Results shows there is no significant difference between each type, particularly on the 1st until 28th day range. However, the growth development of rice weevil S. oryzae are correlated with the types of nutrient used in this study. It is found that rice weevil S. oryzae which that reared in thai red rice show the fastest growth development compared to the other type of rice.